Interrogating Power : Engaged Energy Anthropology - Clarke, Mari H. (Taylor and Francis, 2016)
Human-induced global threats are compelling many anthropologists to rethink roles, methods, and paradigms and engage in public debate and action on energy policies, extraction processes, commodity chains, and consumption. Laura Nader's Energy Reader embodies her decades-long engagement as a catalyst for public debate on U.S. energy issues. Tanja Winther's Impact of Electricity exemplifies ethnography informing development practice. Strauss and colleagues’ Cultures of Energy reflects diverse approaches seeking to build cultural understandings to inform energy choices. There remains a need for collaboration with anthropologists embedded in energy-related agencies—positioned where they can leverage anthropological knowledge to push policy envelopes.